A new strategy to prepare N-doped holey graphene for high-volumetric supercapacitors. Issue 25 (20th May 2016) - Dong, Xinwei; Hu, Nantao; Wei, Liangming; Su, Yanjie; Wei, Hao; Yao, Lu; Li, Xiaolin; Zhang, Yafei
Abstract : N-doped holey graphene with a volumetric capacitance of 397 F cm −3 for supercapacitors was prepared by a novel "Bottom-up" strategy. Abstract : N-doped holey graphene (N-HG) was successfully prepared by a novel "Bottom-up" strategy with scalable and low cost characteristics. The as-obtained N-HG possessed amounts of in-plane holes, a high specific surface area (1602 m 2 g −1 ), a high nitrogen content and could be easily stacked to form a high density carbon monolith which presented a maximum volumetric capacitance of 397 F cm −3 for supercapacitors.